PERBANDINGAN PENERIMAAN PENDAPATAN ASLI DAERAH PADA BADAN PAJAK DAN RETRIBUSI DAERAH KOTA MEDAN TAHUN ANGGARAN 2016-2018 - Munthe, Mario Nicolas (UNIKA Santo Thomas, 2019)
The purpose of this study was to analyze the comparison of the original regional revenue in the Tax Agency and Regional Retribution of Medan City for the 2016-2018 fiscal year. The data used is secondary data obtained from the Regional Financial and Asset Management Agency of Medan City. The analytical tool used is the percentage comparison analysis. The results showed that for: (a) for the 2017/2016 fiscal year showed that the realization of regional tax increased by 24.22 percent, regional retribution decreased by 2.03 percent, revenue from the management of separated wealth areas decreased by 31, 88 percent, and other legitimate local revenues decreased by 25.72 percent. (b) for the fiscal year 2018/2017 shows that the realization of regional tax has decreased by 6.27 percent, regional retribution has decreased by 24.76 percent, income from the management of separated regional wealth has increased by 95.26 percent, and others- other legitimate local revenues increased by 8.39 percent